2014
DOI: 10.1111/vde.12143
|View full text |Cite
|
Sign up to set email alerts
|

Serum autoantibody profiles of IgA, IgE and IgM in canine pemphigus foliaceus

Abstract: Our findings suggest that sera from dogs with PF rarely contain IgA or IgE autoantibodies at levels detectable by indirect immunofluorescence, while IgM autoreactivity appears not to be a feature of this disease. Considering these findings, it appears that canine PF is aetiologically and immunologically similar to that of the classic human PF, in which the IgG autoantibody response is also the predominant type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Furthermore, it is important to note that an association between epidermal-specific auto-antibodies and complement proteins has been described previously in human pemphigus (Lessey et al, 2008;Qian et al, 2011); a cross-reaction among IgE, IgM, and IgG4 anti-DSG-1 response has been reported in human PF patients (Qian et al, 2011). In contrast, IgM autoreactivity was not detected when canine PF serum was used against either DSG-1 or DSC-1 (Bizikova et al, 2014), and canine PF showed dominant IgG auto-antibody reactivity (Pérez et al, 2002: Olivry et al, 2009). Moreover, a previous study also detected IgM-producing B-cells in the extracellular matrix of the dermis and in the intercellular epidermis in canine PF (Pérez et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, it is important to note that an association between epidermal-specific auto-antibodies and complement proteins has been described previously in human pemphigus (Lessey et al, 2008;Qian et al, 2011); a cross-reaction among IgE, IgM, and IgG4 anti-DSG-1 response has been reported in human PF patients (Qian et al, 2011). In contrast, IgM autoreactivity was not detected when canine PF serum was used against either DSG-1 or DSC-1 (Bizikova et al, 2014), and canine PF showed dominant IgG auto-antibody reactivity (Pérez et al, 2002: Olivry et al, 2009). Moreover, a previous study also detected IgM-producing B-cells in the extracellular matrix of the dermis and in the intercellular epidermis in canine PF (Pérez et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…The clinical case described demonstrates the occurrence of pemphigus foliaceous due to pharmacodermic reaction after topical administration of Mupirocin. This disease is known as the most common auto-immune skin disease in dogs and involves the synthesis of antikeratinocyte autoantibodies [3,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…PF is known as the most common autoimmune skin disease in dogs, involving naturally or induced autoantibodies production against desmoglein and desmocolin molecules [1,3]. Iatrogenic PF is subdivided in drug-induced, which drug discontinuance leads to disease regression, or drug-triggered, where the drug stimulates the disease natural development and progression [10,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical signs normally consist of pustules that evolve rapidly into erosions covered with crusts . Histologically, PF is characterized by subcorneal acantholysis, due to IgG autoantibodies against the keratinocyte adhesion molecules; Desmoglein‐1 is a minor autoantigen in dogs with PF . A study reported that desmocollin‐1 represents a major canine PF autoantigen .…”
Section: Introductionmentioning
confidence: 99%